Frugivory on Margaritaria nobilis L.f. (Euphorbiaceae): Poor investment and mimetism - Cazetta, Eliana [UNESP]; Zumstein, Liliane S. [UNESP]; Melo Jr., Tadeu A.; Galetti, Mauro [UNESP] (FapUNIFESP (SciELO), 2008)
Dehiscent fruits of Euphorbiaceae usually have two stages of seed dispersal, autochory followed by myrmecochory. Two stages of Margaritaria nobilis seed dispersal were described, the first stage autochoric followed by ornithocoric. Their dehiscent fruits are green and after they detached from the tree crown and fall on the ground, they open and expose blue metallic cocas. We studied the seed dispersal system of Margaritaria nobilis in a semi-deciduous forest in Brazil. In 80 h of focal observations, we recorded only 12 visits of frugivores, however the thrush Turdus leucomelas was the only frugivore that swallowed the fruits on the tree crown. Pitylus fuliginosus (Fringilidae) and Pionus maximiliani (Psittacidae) were mainly pulp eaters, dropping the seeds below the tree. On the forest floor, after fruits dehiscence, jays (Cyanocorax chrysops), guans (Penelope superciliaris), doves (Geotrygon montana) and collared-peccaries (Pecari tajacu) were observed eating the blue diaspores of M. nobilis. Experiments in captivity showed that scaly-headed parrots (Pionus maximiliani), toco toucans (Ramphastos toco), jays (Cyanochorax chrysops), and guans (Penelope superciliaris) consumed the fruits and did not prey on the seeds before consumption. The seeds collected from the feces did not germinate in spite of the high viability. The two stages of seed dispersal in M. nobilis resembles the dispersal strategies of some mimetic species. However M. nobilis seeds are associated with an endocarp, it showed low investment in nutrients, and consistent with this hypothesis, M. nobilis shared important characteristics with mimetic fruits, such as bright color display, long seed dormancy and protection by secondary compounds.
Keywords: Euphorbiaceae; Frugivory; Mimetic fruits; Secondary compounds; Seed dispersal